2019
DOI: 10.1016/j.ijmultiphaseflow.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of shock-induced flow through stationary particle clouds

Abstract: We investigate the shock-induced flow through random particle arrays using particle-resolved Large Eddy Simulations for different incident shock wave Mach numbers, particle volume fractions and particle sizes. We analyze trends in mean flow quantities and the unresolved terms in the volume averaged momentum equation, as we vary the three parameters. We find that the shock wave attenuation and certain mean flow trends can be predicted by the opacity of the particle cloud, which is a function of particle size an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…The Mach number plots reveal that the flow becomes sonic just upstream of the downstream particle cloud edge. Similar observations have been made in other studies 29,41,43 , and this behaviour is very similar to that found in decreasing pressure. If the duct is sufficiently long, the flow chokes at the downstream exit, just like we observe here.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The Mach number plots reveal that the flow becomes sonic just upstream of the downstream particle cloud edge. Similar observations have been made in other studies 29,41,43 , and this behaviour is very similar to that found in decreasing pressure. If the duct is sufficiently long, the flow chokes at the downstream exit, just like we observe here.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, the flow Mach number increases with downstream distance within the particle cloud 29,31,43 in a manner similar to that observed in Fanno flows 14 . The presence of nearby particles also affects the flow around each particle by changing the direction of the incoming flow, exposing it to particle wakes, etc.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations